REVIEW ARTIKEL : POTENSI FRUKTOOLIGOSAKARIDA DAN INULIN BAHAN PANGAN LOKAL SEBAGAI SUMBER PREBIOTIK - Farindya Dwi Cahyaningtyas; Prima Retno Wikandari (Unesa Journal of Chemistry, 2022)
Prebiotics are a component of food that cannot be digested by human digestion, but can be used as growth nutrients for the intestinal microflora and can provide health benefits. Inulin and fructooligosaccharides (FOS) are types of prebiotics that are widely developed for now. This review aims to determine (1) the potential of inulin and FOS as prebiotics, (2) lactic acid bacteria that can grow on inulin and FOS, and 3) the potential of local food as a source of inulin and FOS. Inulin and FOS are prebiotics because they have β(2-1) bonds so that they have resistance to hydrolysis by acids and enzymes found in the digestive tract and can only be utilized by the intestinal microflora. The results of inulin and FOS metabolism by lactic acid bacteria are able to provide health benefits such as lowering cholesterol and blood sugar levels, lowering blood pressure and inhibiting the growth of pathogenic bacteria. Inulin and FOS can be utilized by several strains of lactic acid bacteria such as Lactobacillus plantarum B1765, Lactobacillus fermentum, Lactobacillus casei, Lactobacilus acidophilus, Leuconostoc mesentroides, Bifidobacterium breve, and Bifidobacterium longum. Inulin and FOS can be found in easily found local foodstuffs such as sweet potatoes, arrowroot, gembili, yam, garlic, dahlia tubers and taro, can be used as growth media for several strains of lactic acid bacteria and provide several health effects so that they can be used as alternative sources of prebiotics